Carbon Dioxide Ice Glaciers at the South Pole of Mars. Issue 4 (26th April 2022) - Smith, I. B.; Schlegel, N.‐J.; Larour, E.; Isola, I.; Buhler, P. B.; Putzig, N. E.; Greve, R.
Abstract: Massive, kilometer thick deposits of carbon dioxide (CO2 ) ice have been detected at the south polar cap of Mars by radar investigations. These deposits are divided into several units that are separated by thin water ice bounding layers. Recent studies investigated the accumulation history of CO2 ice and found that the deposits most likely formed during several episodes in the past, when Martian obliquity was much lower than now. Those studies, while able to predict total volumes of CO2 ice consistent with those observed, did not attempt to explain the anomalous three‐dimensional distribution (thickness or extent) of CO2 ice or the ice's offset from the topographic high of the polar cap. In this paper we use a combination of feature analysis and numerical modeling to demonstrate that the CO2 deposits flow as glaciers and that glacial flow distributes the ice into its current position. Further, this distribution allows the ice to survive during high obliquity excursions. Plain Language Summary: Carbon dioxide (CO2 ) ice is found in a stack of deposits at Mars' south pole. These deposits are situated in basins, where they reach more than 1 km thick. Previous work suggested that the CO2 ice should be deposited when the axial tilt of the planet was lower, making the poles colder than they are now; however, the thickness and distribution of this ice should be much thinner than observed if only atmospheric effects are working on the ice. Therefore, the CO2 ice deposit distribution cannot be explained by atmospheric deposition alone. In this paper, we use glacial modeling and feature analysis to demonstrate that glacial flow better explains the distribution of ice in its present state. In addition, we show that the slopes on the south polar cap act to focus glacial flow into the basins, where it can survive warm periods by sublimating only the uppermost sections when the tilt of the planet is larger than present day. Key Points: Carbon dioxide ice has been mapped and modeled at the south pole of Mars Deposition models cannot explain the volumetric distribution of CO2 ice, thickness, or distribution We present geomorphic and modeling evidence that the CO2 deposits flow as glaciers into basins to reach their observed volumetric distribution